The Correlation Between the Level of Dependence and The Risk of Decubitus in Stroke patients in the Inpatient Room of Dr. Haryoto Lumajang: HUBUNGAN TINGKAT KETERGANTUNGAN DENGAN RISIKO TERJADINYA DEKUBITUS PADA PASIEN STROKE DI RUANG RAWAT INAP RSUD DR. HARYOTO LUMAJANG - Prawita Hadi Muzakki; Achmad Kusyairi; Dodik Hartono (Journal of Nursing Care and Biomolecular, 2023)
Introduction: Immobilization is the inability to move positions or bed rest for 3 days or more with the movement of the body's anatomy disappearing due to changes in physiological functions such as stroke patients, and become dependent on living their lives. The level of dependency on the patient's mobility is a factor that directly affects the risk of dekubitus. Method: The purpose of this study was to determine the correlation between the level of dependence and the risk of decubitus in stroke patients in the Inpatient Room of RSUD dr. Haryoto Lumajang. The research design is correlational analytic with a cross-sectional method. This research was conducted in the Inpatient Room of Dr. Haryoto Lumajang on February 6, 2023 – March 10 2023. The study population consisted of 39 stroke patients, the sample was 36 respondents that was taken by accidental sampling. The research instrument used a dependency level questionnaire (Barthel index) and a Braden scale observation sheet. Result and Analysis: The results showed that stroke patients had a moderate level of dependency, namely 14 respondents (38.9%), and high-risk dekubitus, namely 14 respondents (38.9%). The Spearman's Rank correlation test results obtained p <0.05 (p = 0.000; α = 0.05), so it can be concluded that there is a correlation between the level of dependence and the risk of dekubitus in stroke patients in the inpatient room of dr. Haryoto Lumajang. Discussion: It is hoped that nurses can carry out an initial assessment of skin integrity, especially in cases of stroke patients who often experience immobilization. With proper care and appropriate prevention, the risk of developing decubitus in patients both in the hospital and upon discharge from the hospital will decrease. Keywords: Dependency Level, Decubitus Risk, Stroke